Polygraphic Counterproductive Behavior Index Profiling System - Yusoff, Hashim; Abu Bakar, Ahmad Zaki; Alias, Rose Alinda (2006)
Various tools have been employed to help detect counterproductive behaviors including the use of polygraph techniques. The purpose of this paper is to study, design and develop a proof-of-concept polygraphic counterproductive behavior index profiling system for human resource selection besides building and developing polygraphic repository of counterproductive behavior index profile. 10 major areas will be covered namely alcohol use, computer abuse, credibility, customer service, fundamental data, illegal drug use, sexual harassment, theft propensity, work attitude, and work history. Scale scores of 1 to 10 will be developed which will be further divided into 3 major areas of concerns, namely little or no concerns (Angel), normal concerns (Human) and serious concerns (Devil). Lower scorers are of little or of no concerns. Medium scorers are of normal concerns while higher scores are of serious concerns. Information system research design framework will be utilized for the purpose.